HUbis: heurísticas de usabilidade para avaliar sistemas ubíquos - Rocha, Larissa Castro (2017)
In the paradigm of ubiquitous systems, computing technologies must be invisible to the users and bring benefits to their daily activities. For this, these systems should be incorporated into several everyday objects, interacting with the users discreetly and providing services according to their current context. Because of this change in the mode of interaction between the ubiquitous system and the user, evaluating the usability of these systems becomes essential to ensure their acceptance. One of the methods of the Human-Computer Interaction (HCI) used to evaluate the usability of systems is the Heuristic Evaluation (HE), which consists of an inspection by specialists, who follow usability guidelines and evaluate the interfaces of the systems with the aim of finding usability problems. The Nielsen’s heuristics (NH), which are widely used in HE of conventional systems (i.e., desktop, web), do not focus on the particularities of ubiquitous systems such as mobility and context-awareness. Therefore, usability problems related to these aspects may not be identified. Based on an existing process that establishes heuristics for specific domains, this work then proposes usability heuristics to evaluate ubiquitous systems (HUbis), considering not only the specific characteristics that influence the HCI of these systems but also the NH. In order to evaluate HUbis, on one hand, an empirical study is carried out to explore the proposed heuristics, observing their use in HE. On the other hand, questionnaires are used with the purpose of collecting expert considerations about the HUbis creation process. From the analysis of the results of these two evaluations, the heuristics are refined. Furthermore, a guide is also presented, so the community can better use the HUbis in HE, considering the particular aspects of ubiquitous systems.